Association of blood glucose and renal end points in advanced diabetic kidney disease. (March 2020) - Kornelius, Edy; Lo, Shih-Chang; Huang, Chien-Ning; Wang, Yu-Hsun; Yang, Yi-Sun
Abstract: Aims: The association of blood glucose in advanced diabetic kidney disease (DKD) is unclear. This study investigated the association between blood glucose and renal endpoints in DKD patients. Methods: This retrospective cohort study enrolled type 2 diabetic patients with advanced DKD with an estimated glomerular filtration rate (eGFR) between 30 and 90 ml/min/1.73 m2 and urine albumin-to-creatinine ratio (UACR) of 300–5000 mg/g. We classified patients into 2 groups according to their 1-year average HbA1c: <7% and >7%. We followed up the patients until the occurrence of primary renal endpoints. Results: A total of 345 patients were included in the analysis for the period 2012–2018. Mean baseline eGFR was 58 ml/min/1.73 m2 and mean albuminuria levels were 1146 and 1313 mg/g, respectively. Median study duration was 3 years. The risk of primary renal endpoints was not decreased in patients with HbA1c less than 7% with an adjusted hazard ratio (aHR) of 0.62, 95% CI 0.26–1.45. The risks of persistent eGFR lower than 15 ml/min/1.73 m2 and doubling of serum creatinine level were similar between 2 group with aHR of 0.58 (95% CI 0.19–1.83) and 0.61 (95% CI 0.26–1.44), respectively. Conclusions: Intensive blood sugar control did not prevent renal failure in advanced DKD.